The Role of Capital Structure on The Effect of Dividend Policy and Business Risk on Firm Value (Evidence from Indonesian Manufacturing Company) - Anggit Esti Irawati; Erna Fitri Komariyah (The Indonesian Journal of Accounting Research, 2019)
This study examines the effect of dividend policy and business risk on firm value and capital structure. Moreover, this study analyzes the role of capital structure on that relationship simultaneously. The relationship between these variables has been a debate in the capital market literature. Using manufacturing companies listed on Indonesia Stock Exchange (IDX) for years 2012-2018, this study takes into account that the dividend policy and business risk does not directly impact to the firm value. Thus, we examine 41 companies that meet the sample criteria. The result show that dividend policy and business risk have a positive effect both on firm value and capital structure. Then, capital structure has a role to mediating the effect of dividend policy and business risk on firm value has been confirmed.